2021
DOI: 10.7717/peerj.11968
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel survival model for acute myeloid leukemia based on autophagy-related genes

Abstract: Background Acute myeloid leukemia (AML) is one of the most common blood cancers, and is characterized by impaired hematopoietic function and bone marrow (BM) failure. Under normal circumstances, autophagy may suppress tumorigenesis, however under the stressful conditions of late stage tumor growth autophagy actually protects tumor cells, so inhibiting autophagy in these cases also inhibits tumor growth and promotes tumor cell death. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…In contrast, LAML patients with a high infiltration level of NK cells had poorer overall survival than those with a low infiltration level ( p = 0.0449, Fig. 6 D), which was consistent with the study's results [ 44 ] that the NK cells activated with high expression were associated with a poor prognosis. In addition, we also found that several unknown cell types had an impact on the survival of cancer patients (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In contrast, LAML patients with a high infiltration level of NK cells had poorer overall survival than those with a low infiltration level ( p = 0.0449, Fig. 6 D), which was consistent with the study's results [ 44 ] that the NK cells activated with high expression were associated with a poor prognosis. In addition, we also found that several unknown cell types had an impact on the survival of cancer patients (Fig.…”
Section: Resultssupporting
confidence: 91%
“…All mRNA expression-associated data were transformed by log 2 (x + 1). Datasets with the same platform (e.g., GSE32036 and GSE4127 from GPL6884) were merged for a combined dataset after eliminating batch effects [13][14][15][16], which was similar to the published study [12].…”
Section: Data Standardization and Elimination Of Batch Effects Betwee...mentioning
confidence: 99%
“…To detect associations between ITGAV expression and tumor immune microenvironment (TME), the relationship between ITGAV expression and immune infiltration levels (using Pearson coefficient) was explored based on the ESTIMATE algorithm [19,[21][22][23] and CIBERSORT algorithm [14,24,25]. Immune checkpoints were promising in the treatment of cancers [26], and thus, the study also evaluated their associations with ITGAV expression to preliminarily assess the immunotherapy potential of ITGAV in SCLC.…”
Section: The Potential Mechanisms Of Itgav In Sclcmentioning
confidence: 99%
“…Decreased Beclin-1 and p62 levels are associated with unfavorable outcomes of AML [ 135 ], suggesting the potential of autophagy genes as biomarkers for hematologic tumors. Although the evidence is inadequate, studies have supported the mediation of AML tumorigenesis by the bioinformatic tools through prediction of risk scoring based on autophagy gene signatures [ 136 , 137 ]. In addition, profiling of genome-wide alternative splicing (AS) events in the AML cohort of The Cancer Genome Atlas indicates that survival-related AS events are enriched in leukemia-associated gene sets, including the autophagy pathway [ 138 , 139 ].…”
Section: Introductionmentioning
confidence: 99%
“…Univariate Cox regression analysis and least absolute shrinkage and selection operator (LASSO) regression identified a six-gene signature ( CASP3, CHAF1B, KLHL24, OPTN, VEGFA, and VPS37C ) predictive of AML progression and survival [ 137 ]. A recent bioinformatics study using 10 ATGs for prediction of AML prognosis showed that groups at high risk of AML have higher expression of immune checkpoint genes and a greater proportion of CD4 T and NK cells [ 136 ]. According to univariate Cox regression analysis of the transcriptomic profiles of patients with AML, 32 ATGs were significantly associated with OS.…”
Section: Introductionmentioning
confidence: 99%